Post-synthesis of a covalent organic framework nanofiltration membrane for highly efficient water treatment. Issue 42 (16th October 2019) - Liu, Chuanyao; Jiang, Yunzhe; Nalaparaju, Anjaiah; Jiang, Jianwen; Huang, Aisheng
Abstract : A novel covalent organic framework (COF) IISERP-COOH-COF1 membrane with both high water permeance and high ions rejection was developed for desalination through post-modification, which shows superior ions rejection based on size exclusion. Abstract : Nanofiltration (NF) membranes with ultrahigh water flux and high ion rejection are substantially beneficial for desalination and wastewater treatment. However, synthesis of NF membranes with high water permeance while maintaining high ion rejection remains a great challenge. Herein, we report a highly stable covalent organic framework (COF) IISERP-COOH-COF1 membrane with high ion rejection and relatively high water flux. Through post-modification, the pore aperture of the IISERP-COOH-COF1 membrane can be constricted, thus preventing ions from accessing the pores. Further, covalent post-functionalization is helpful to reduce non-selective transport through invisible intercrystalline defects, thus enhancing salt rejection. Demonstrated by both experimental and simulation studies, the IISERP-COOH-COF1 membrane shows superior ion rejection ( e.g., 96.3% for Na2 SO4, 97.2% for MgSO4, 99.6% for FeCl3, 90.6% for MgCl2, and 82.9% for NaCl) based on size exclusion, with a water flux above 0.5 L m −2 h −1 bar −1 .